WORKSHOP PARENTING: SINERGITAS ORANG TUA DAN GURU PAUD DALAM MENGENALI POTENSI ANAK DI TK SYAICHONA KHOLIL BALIKPAPAN - Jamilah (PENDALAS: Jurnal Penelitian Tindakan Kelas dan Pengabdian Masyarakat, 2021)
Abstract: Our children are our future investments. Shaping a child's character is the responsibility of parents. Efforts to shape the character of children through education have been done since time immemorial. Various studies are also conducted to streamline the character formation process. However, the obstacles that come from the role of teachers and parents themselves are still an urgent problem. Early childhood students who are students on non-formal education paud and kindergarten. The learning a child receives is something new to them. In PAUD and Kindergarten more fun activities by playing while learning to read and write. This makes the barriers even more numerous. This community service activity seeks to answer the problem. The results obtained show that parenting activities are very important for parents. Various concerns of paud and kindergarten students about their respective children can be conveyed and discussed properly. Through this activity can increase the awareness of student guardians to establish cooperation with teachers and school well to realize maximum child development.